Scrutinizing Students’ Perspectives on Digital Storytelling as an Educational Tool in Learning English - Asnas, Sania Alinda Mouli (Journal of Languages and Language Teaching, 2024)
English Teachers encounter difficulties when trying to pique students' interest in learning English. Technological innovations can enhance English courses through digital storytelling, which can support English lessons because it can strengthen students' commitment to learning and foster a better learning atmosphere. Therefore, this study aims to explore students' views of the attitudes and barriers when leveraging digital storytelling in learning English. This research utilized qualitative methods with questionnaire and interview research instruments to fill the methodological gap because there was a lot of research on digital storytelling conducted using quantitative methods. There were forty eighth-grade students at a private junior high school in Malang who had filled out the questionnaire, and three of them were interviewed. The research results showed that when leveraging digital storytelling to learn English, they have a favorable perspective concerning it, such as assisting them in focusing on the lesson material, keeping them entertained, aiding them in visualizing the lesson material, deepening their understanding of the lesson material, engaging them in learning, helping them communicate in English, providing them a sense of security to take part in class, and creating a stimulating learning environment. On the other hand, some students displayed uncertainty in terms of self-confidence and self-motivation when learning English leveraging digital storytelling although some students also demonstrated an increase in these traits. In addition, by leveraging digital storytelling, they found it simpler to recall the information given and felt more at ease expressing their language proficiency in the form of listening, speaking, reading, and writing. However, they ran into barriers while leveraging digital storytelling in English classrooms, including technological issues and trouble understanding unfamiliar vocabulary. The study’s implications have been mentioned here.